Laugh with us, not at us: Parody and networked learning - Sinclair, Christine (Proceedings of the International Conference on Networked Learning, 2018)
In keeping with its theme, this paper has a light touch and a serious point. It arose from a concern that networked learning may not be recognisable enough to be parodied. Parody is a pervasive and ubiquitous cultural practice that entails imitation and laughter – features which could perhaps contribute to making networked learning knowable to a wider community. Despite parody’s potential for serious damage, its broadest use supports the recognition, consolidation, development and renewal of a genre or movement. Drawing on Bakhtinian notions of the dialogic and carnival, as well as the light thrown on contemporary discourse through Bakhtin’s literary insights, the paper explores the extent to which networked learning artefacts and practices engage in parody and have been parodied. A thought experiment to parody a networked learning conference paper led to the current paper’s structure. This attempt to parody highlights the difficulties of departing from conventional academic genres even in a field of study that challenges those genres. The study identifies how themes of genre, intertextuality and multimodality combine in papers and events about networked learning to produce texts and practices that are open to renewal, hacking and augmentation, but without the need for the laughter that comes with parody that might have the same results. In papers and book chapters, although there are lively forms of writing, heavy use of citation is the main source of intertextuality. Evidence of parody was found in a symposium, including (self) parody of networked learning conference practices, suggesting that we are more likely to find parody during synchronous events than in peer reviewed academic texts. An almost accidental result of the parodied structure of the paper suggests that networked learning could be developing in a way that parallels Bakhtin’s understanding of the novel, yet without the cultural work that parody has contributed to the novel. This line of reasoning brings into sharper focus one of the key features of this author’s own initial parody of networked learning: its emphasis on boundaries and boundary crossing. It seems that networked learning, like the novel, cannot be parodied as a ‘complete’ form: like the novel it is constantly changing to reflect its contemporary world.